Analisis Gerakan Sosial Baru: Studi Kasus Gerakan Black Lives Matter Terhadap Pemilihan Presiden Amerika Serika Tahun 2020 - Nafila Reydha Mahisa; Alfian Hidayat; Ahmad Mubarak Munir (Indonesian Journal of Global Discourse, 2021)
This research aims to explore the analysis of the New Social Movement Black Lives Matter which fights for racial justice and defends the rights of black people in the United States and throughout the world. Black people experienced injustice and systemic events carried out by the United States Government with many police cases and murders that killed black people that occurred during the Donald Trump era. Black Lives Matter conducts protests and campaigns to fight for its mission. By using the theory of new social movements according to the thoughts of Ernesto Laclau and Chantal Mouffe and the concept of Connective action by Bennett and Segerberg as an analytical knife, this paper will dissect the Black Lives Matter social movement to find out the pattern of movement, substance, actors involved and the strong discourse spread by Black lives matter so that it can mobilize the masses and influence the 2020 United States presidential election as an effort to make social change, namely achieving racial justice in the United States and the world.